Fabrication Of Tic-Reinforced Iron Based Composite Through Mechanical Activation And Carbothermal Reduction Of Hematite And Anatase - Hassin, Mohd Salihin (2012)

(untitled)
In this research, the influence of milling time and sintering temperature on TiCreinforced iron composite formation by carbothermal reduction of hematite (Fe2O3) and anatase (TiO2) mixture was investigated. Mixtures of Fe2O3, TiO2 and graphite powders with composition of Fe-30%TiC were mechanically activated in a high energy ball mill at various milling times (0 hour-60 hours). X-ray diffraction (XRD) analysis of as-milled powder showed broadening of Fe2O3 peaks with disappearance of TiO2 and graphite peaks due to powder refinement and diffusion of graphite. Longer milling time resulted in a reduction of crystallite size of Fe2O3 down to nanometer range and an increment in both internal strain and dislocation density. After 60 hours milling, magnetite (Fe3O4) peaks appeared in the XRD pattern as a result of partial reduction of Fe2O3. The as-milled powder was compacted by cold pressing under 200 MPa and sintered in argon atmosphere at various sintering temperature (1100°C-1400°C). High temperature sintering resulted in formation of Fe and TiC phases as confirmed by X-ray diffraction and energy dispersive X-ray analyses. Without mechanically activated milling, the reaction to form TiC only occurred at 1400°C during sintering indicating a reduction of temperature has been promoted by mechanical milling. Fe-TiC composite prepared with longer milling time and higher sintering temperature (50 hours and 1400°C) showed the highest density and hardness which is due to the fineness of the composite powder, together with complete TiC and iron phases formation. Formation of Fe3O4 in the as-milled powder after 60 hours milling reduced the density and hardness of Fe-TiC composite as a result of pores formation in the composite.